Digital Rights Management and Cultural Institutions: Case Study New York Public Library Library for the Performing Arts - Eschenfelder, Kristin R. (My University, 2010)
The Digital Rights Management and Cultural Institutions Project was funded by an Institute of Museum and Library Services (IMLS) grant 04-06-0029-06 to investigate the impact of digital rights management technologies on the development of digital collections in U.S. archives, libraries and museums. The case studies portion of the project identified six exemplary projects that employed a variety of rights management technologies and policies to serve as examples from which other institutions might learn. The New York Public Library Library for the Performing Arts describes a case study of a controlled collection of videos of dance performances and related materials
Keywords: dance performance; donor relations; privacy; copyright; technological protection measure; digital rights management; digital library